2014
DOI: 10.1186/preaccept-1104918955137141
|View full text |Cite
|
Sign up to set email alerts
|

Lipid index changes in the blood serum of patients with hyperplastic and early neoplastic lesions in the ovaries

Abstract: Background: The authors used the lipid index (WL) to monitor lipid changes before and after surgery. The surgical operation performed was the simultaneous enucleation of a cystic tumor of the hilum ovarii in its entirety (with diagnosis of a simple cyst or teratoma adultum) in groups of 20 patients. Objectives: To compare the lipid index WL in the blood serum of patients undergoing surgery treatment at the following times: before and 7 days after surgery, and 6 and 12 months after surgery. Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the present research the usability of lipid indices was shown in women who underwent gynaecological surgeries during menopause [9] and with pathological changes within ovaries. The lipid index WS has recently been described, and it has been successfully used in ovarian cancer diagnostics [12,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the present research the usability of lipid indices was shown in women who underwent gynaecological surgeries during menopause [9] and with pathological changes within ovaries. The lipid index WS has recently been described, and it has been successfully used in ovarian cancer diagnostics [12,17,18].…”
Section: Discussionmentioning
confidence: 99%